Turbulent Thermal Image Velocimetry at the Immediate Fire and Atmospheric Interface. Issue 24 (10th December 2021) - Katurji, Marwan; Zhang, Jiawei; Satinsky, Ashley; McNair, Hamish; Schumacher, Benjamin; Strand, Tara; Valencia, Andres; Finney, Mark; Pearce, Grant; Kerr, Jessica; Seto, Daisuke; Wallace, Hugh; et al.
Abstract: We present novel in‐field vegetation fire observations and the analyses using brightness temperatures recorded by longwave infrared camera and thermal image velocimetry. The brightness temperatures from a wind‐driven stubble wheat fire were obtained with a 60 frames per second (fps) video acquisition. Multi‐level sonic anemometers on a 10m in‐fire tower were used for measurements of turbulent velocity and air temperatures, while fuel level air and flame temperatures were collected by an array of thermocouples (TCs). The camera's image pixel resolution was adequate to discern thermal structures in accordance with the in‐fire TC measurements and its spacing distances. The in‐situ and remotely measured flaming zone dynamics were derived using two different methodologies, Thermal Image Velocimetry (TIV) and Image Segmentation (IS). The results highlight spatial and spectral information of coherent turbulent and mean velocity structures. The power spectra decomposition of the TIV showed similar spectral characteristics to the sonic speed measurements during the fire passage under the tower with a similar inertial subrange slope. This result reveals plausible evidence of interaction between the flaming zone and wind turbulence for a prescribed rapidly moving stubble wheat fire. This research presents a new field measurement methodology for understanding fire‐atmospheric interactions between the flaming zone and the immediate overlying atmospheric turbulent boundary layer. Plain Language Summary: The size and destructive power of wildfires can vary depending on weather and fuel conditions. We have carried out wheat stubble burning experiments using specialized instrumentation in order to study how the wind and fire interact, and the subsequent role of this interaction in the development of an experimental field‐scale burn. We used Long‐Wave InfraRed or LWIR cameras to capture radiation emitted by the fire but invisible to the human eye. We then used the time‐sequenced LWIR images to detect and calculate forward motion and fluctuation of the fire. We demonstrated for the first time the validity of these techniques by comparing the results with wind measurements collected during the passage of the fire using sonic anemometers. This new observation method has provided the first set of two‐dimensional observations of the interaction between the flame zone and the overlying wind. Key Points: A near target cooled infrared camera captures spatial fire thermal perturbations verified with an onsite thermocouple sensor array Turbulence derived from Thermal Image Velocimetry of flaming zone reveals similar spectral characteristics with atmospheric measurements